2002
DOI: 10.1046/j.1365-2648.2002.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Swiss nurses' knowledge related to health care reforms: an exploratory study

Abstract: Overall, data showed a moderate to high mean level of knowledge (around 70% correct responses) on all knowledge scales considered. Community setting, managerial position, and a nonacademic nursing degree were all positively related to higher levels of reforms' knowledge. On the contrary, employment in a hospital setting and having a university degree had both negative impacts on achieving a high score of knowledge. Levels of certainty were significantly higher for LAMal than NOPS and for correct rather than fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The results showed that most of the sample had high and very high levels of overall knowledge about the national health policy development process. The results of this study are similar to those in the study by Spitzer et al. (2002), who explored the knowledge level of 74 nurses regarding Switzerland's health reform policy.…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that most of the sample had high and very high levels of overall knowledge about the national health policy development process. The results of this study are similar to those in the study by Spitzer et al. (2002), who explored the knowledge level of 74 nurses regarding Switzerland's health reform policy.…”
Section: Discussionsupporting
confidence: 85%
“…In this study representing all provinces of Finland and different sectors of the health care industry, only eight percent of the nurses estimated their opportunities to be involved in the organizational restructuring that had taken place at their own workplaces as good. The result is parallel to earlier studies indicating poor inclusion of nurses in health care restructuring in several Western societies (1)(2)(3)(4) and is thus hardly surprising.…”
Section: Discussionsupporting
confidence: 84%
“…Evidence shows that the inclusion of nurses in health care restructuring has traditionally been poor (1)(2)(3)(4). At the macro-level the power to create political discourses and to build health care restructuring processes is usually limited to a dominant few.…”
Section: Introductionmentioning
confidence: 99%
“…Where research has focused on the clinicians' perspective, study findings have shown that clinical nurses are unable to resist or revolt in the setting of reform because they are too exhausted (Keddy et al . 1999) or they have significantly low levels of reform knowledge (Spitzer et al . 2002).…”
Section: Introductionmentioning
confidence: 99%